Rapid and simple preparation of thiol–ene emulsion-templated monoliths and their application as enzymatic microreactors1. Issue 10 (21st May 2015) - Lafleur, Josiane P.; Senkbeil, Silja; Novotny, Jakub; Nys, Gwenaël; Bøgelund, Nanna; Rand, Kasper D.; Foret, Frantisek; Kutter, Jörg P.
<x xml:space="preserve">Abstract</x> A novel, rapid and simple method for the preparation of emulsion-templated monoliths in microfluidic channels based on thiol–ene chemistry is presented.